Less is more: adaptation of voltage after battery replacement in deep brain stimulation for dystonia - Blahak, Christian; Capelle, Hans-Holger; Bäzner, Hansjörg; Kinfe, Thomas M.; Hennerici, Michael G.; Krauss, Joachim K. (Stereotactic and functional neurosurgery, 2010)
Background: To maintain the efficacy of deep brain stimulation (DBS) on dystonic symptoms, slight incremental increase in voltage may be necessary over years after a steady state has been reached following the initial programming of optimal settings. So far however, no data are available regarding the adjustment of voltage after implantable pulse generator (IPG) replacement to achieve sustained optimal control of dystonia with the least side effects. Methods: We analyzed stimulation settings before and after IPG replacement for battery depletion (n = 61) in 18 patients with chronic DBS of the globus pallidus internus or the ventral intermediate nucleus of the thalamus for dystonia. Results: The stimulation intensity could be significantly reduced by 24.8% after IPG replacement. The amount of voltage reduction was equal between bipolar and monopolar stimulation modes (24.9 vs. 24.3%, p = 0.89) and significantly correlated with the magnitude of stimulation intensity before IPG replacement (ρ = 0.429, p = 0.001). Conclusions: After IPG replacement, in patients with DBS for segmental dystonia the voltage can be reduced by approximately 25%. This phenomenon might be explained by a gradual decrease in the electrical energy effectively delivered by the IPG in the course of the lifetime of the battery or neuroplastic processes in particular in the period around battery replacement.
Gesehen am 12.03.2021